2021
DOI: 10.13060/23362839.2021.8.1.520
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Private Rental Housing Market in Poland: What Do Experts Say and What Do Actual Data Show?

Abstract: The aim of the article is to determine the impact of the COVID-19 pandemic on the level of housing rents using the example of the City of Krakow. This study is based on objective data on rental prices and subjective information obtained from real estate agents using a questionnaire survey. The research revealed that the first wave of the COVID-19 pandemic actually led to a 6-7% decrease in prices in the rental market in Krakow, while at the same time the surveyed real estate agents had estimated that rents wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…Marona and Tomal [10] found that the COVID-19 pandemic had a considerable impact upon the workflow of real estate brokers and their clients' attitudes in the city of Krakow, Poland. Another research work of theirs revealed that the first wave of the COVID-19 pandemic actually led to a 6-7% decrease in prices in the rental market in Krakow [11]. Del Giudice et al [12] developed a real estate pricing model to evaluate the short and mid-run effects of COVID-19 on housing prices in the Campania Region, Italy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marona and Tomal [10] found that the COVID-19 pandemic had a considerable impact upon the workflow of real estate brokers and their clients' attitudes in the city of Krakow, Poland. Another research work of theirs revealed that the first wave of the COVID-19 pandemic actually led to a 6-7% decrease in prices in the rental market in Krakow [11]. Del Giudice et al [12] developed a real estate pricing model to evaluate the short and mid-run effects of COVID-19 on housing prices in the Campania Region, Italy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, especially during the first wave, the mortgage market froze, and banks started to increase credit requirements. In the case of Poland, the substantial impact of the pandemic on stock returns during its second and third waves may be due to the fact that the government introduced very farreaching restrictions in this period (Tomal and Marona 2021). At the same time, however, the impact strength of the pandemic on the volatility of stock returns in Poland decreased, which indicate that market participants in the wake of the increased incidence of the disease tried to limit their actions in the stock market compared to the period of the first wave.…”
Section: Resultsmentioning
confidence: 99%
“…Despite speculation concerning the importance of the COVID-19 crises for urban housing markets ( Batty, 2020 ; Goodman and Magder, 2020 ; Tanrıvermiş, 2020 ; Tomal and Marona, 2021 ), we are not aware of any study examining how the outbreak of the pandemic has altered the formation of residential urban submarkets. To fill this research gap, our objective was to analyze changes in the factors that determine the rental prices and the spatiotemporal structure of housing submarkets before and during the COVID-19 pandemic in Cracow, Poland.…”
Section: Introductionmentioning
confidence: 99%